THE POTENTIAL RELATIONSHIP BETWEEN PIMOZIDE AND CHOLESTATIC HEPATITIS - Eker, Salih Saygin; Akkaya, Cengiz; Sarandol, Asli; Yusufoglu, Canan; Kirli, Selcuk (Journal of Pakistan Psychiatric Society, 2008)
We describe a 40 year-old woman who was diagnosed as a case of Major Depressive Disorder with Psychotic Features. Patient’s physical examination and laboratory tests revealed no abnormalities at the time of admission. Just after two days of addition of pimozide to the ongoing therapy, jaundice and elevated liver enzymes were detected which may indicate a drug induced hepatitis. Serologic tests, hepatobiliary ultrasonography and pelvic MRI were performed and no abnormality was detected. Patient was diagnosed with drug induced cholestatic hepatitis by gastroenterology department. Following discontinuation of all drugs, liver enzymes were gradually normalized and jaundice resolved.